Baseline HbA1c predicts attainment of 7.0% HbA1c target with structured titration of insulin glargine in type 2 diabetes: a patient‐level analysis of 12 studies. Issue 9 (5th April 2013) - Riddle, M. C.; Vlajnic, A.; Zhou, R.; Rosenstock, J.
<x xml:space="preserve">Abstract</x> Aims To determine whether baseline characteristics, especially haemoglobin A1c (HbA1c), predict the likelihood of reaching HbA1c ≤ 7.0% or the risk of experiencing hypoglycaemia after the addition of insulin glargine to oral therapy in type 2 diabetes. Methods Pooled patient‐level data from 12 prospective, randomized, controlled studies that used insulin glargine in a treat‐to‐target titration regimen seeking fasting glucose levels ≤5.5 mmol/l (100 mg/dl) were analysed. Baseline characteristics were evaluated by logistic regression models as predictors of reaching a target HbA1c ≤ 7.0% or experiencing confirmed hypoglycaemia. The effect of prior glycaemic control was further explored by analysis of categorical ranges of baseline HbA1c. Results Of 2312 participants, 95% completed 24 weeks of treatment. Lower HbA1c at baseline was independently associated with reaching HbA1c target [adjusted odds ratio (OR) for 1% difference: 0.538, p < 0.0001] and also with likelihood of experiencing confirmed hypoglycaemic events (adjusted OR: 0.835, p < 0.0001) at week 24. In an unadjusted analysis by baseline HbA1c range, the strong association between baseline control and attaining target HbA1c was confirmed (75% with baseline HbA1c < 8.0%, 60% with baseline HbA1c ≥ 8.0 and <9.0% and 38% with baseline HbA1c ≥ 9.0% attained HbA1c ≤ 7.0%). The incidence of hypoglycaemia confirmed <3.9 mmol/l (70 mg/dl) was higher in the lower baseline HbA1c ranges but severe hypoglycaemia was infrequent at all baseline HbA1c levels. Conclusions Systematically titrated insulin glargine, added to oral agents, was effective over a wide range of baseline HbA1c. Lower baseline HbA1c was the best clinical predictor of achieving HbA1c ≤ 7.0% and also associated with higher risk of glucose‐confirmed hypoglycaemia. Severe hypoglycaemia was infrequent using this treatment approach.